Energy demand of synaptic transmission at the Hippocampal Schaffer-Collateral Synapse - Liotta, Agustin; Kann, Oliver (Journal of cerebral blood flow & metabolism, 2012)
Neuroenergetic models of synaptic transmission predicted that energy demand is highest for action potentials (APs) and postsynaptic ion fluxes, whereas the pres...
Article first published online: August 29, 2012
Gesehen am 20.11.2018